(untitled) (JURNAL PROTEKSI KESEHATAN, 2023)
Neck pain can be caused by ergonomic factors such as doing activities that cause the neck to be in a static position and experiencing repetitive motion for a long time. This study aims to determine the prevalence and risk factors for neck pain in college students. An analytic observational study with a cross-sectional approach was used to 231 UIN Jakarta Public Health students aged ≥18 years. Data was collected through an online questionnaire and analyzed by the chi-square test. The results showed the prevalence of neck pain in college students was 25% with the duration of using a laptop/computer as a risk factor that was significantly associated with the incidence of neck pain (pv = 0.02). The prevalence of neck pain in college students is still quite high. There is a need for education related to risk factors for neck pain among students, especially those who conduct online lectures.